2021
DOI: 10.5334/irsp.571
|View full text |Cite
|
Sign up to set email alerts
|

Are Past and Future Selves Perceived Differently from Present Self? Replication and Extension of Pronin and Ross (2006) Temporal Differences in Trait Self-Ascription

Abstract: We attempted a pre-registered replication and extension of Studies 1, 2, and 3 from Pronin and Ross (2006) regarding the effects of social and temporal distance on trait attributions with an online American Amazon MTurk sample (N = 911). We concluded mixed findings. We found support for the original findings: participants attributed more dispositional traits to others compared to themselves, although with weaker effects (original: f = 0.35, 95% CI [0.09, 0.61]; replication: f = 0.10, 95% CI [0.03, 0.16]). Also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…Since the four dimensions of psychological distance operate using similar cognitive mechanisms and have similar effects on perception, evaluations, and action ( Trope and Liberman, 2010 ; Adelina and Feldman, 2021 ), similar effects on spontaneous justice inferences should be obtained with other dimensions, such as social distance or hypotheticality. However, Ham and van den Bos (2008) found that personal relevance influenced spontaneous justice inferences.…”
Section: Discussionmentioning
confidence: 99%
“…Since the four dimensions of psychological distance operate using similar cognitive mechanisms and have similar effects on perception, evaluations, and action ( Trope and Liberman, 2010 ; Adelina and Feldman, 2021 ), similar effects on spontaneous justice inferences should be obtained with other dimensions, such as social distance or hypotheticality. However, Ham and van den Bos (2008) found that personal relevance influenced spontaneous justice inferences.…”
Section: Discussionmentioning
confidence: 99%
“…), so that we can instead focus on the implications regarding specific designs and found effects. This design has been tested and shown to be successful in several recent replications (Adelina & Feldman, 2021;Chandrashekar et al, 2021;Chen et al, 2021;Ziano et al, 2021).…”
Section: Design and Proceduresmentioning
confidence: 99%